Evaluation of an Advanced Health Assessment Course for Acute Care Nurse Practitioners - B. O'Farrell, M. Ford-Gilboe and C. Wong (Nursing Leadership, 2000)
The Acute Care Nurse Practitioner (ACNP) role is being implemented in many centres in Canada. Administrators need to be aware there are very few universities in Canada that prepare ACNPs for advanced health assessment. Therefore, a need may exist for continuing education in the work environment. The ACNPs in London, Ontario recognized such a need, and developed and implemented an Advanced Health Assessment Course using available resources, and administrators supported participation in the course. A pre-post course evaluation based on Bandura's Self-Efficacy theory (1997) was performed. From pre-test to post-test there were significant increases in: (a) the use of health assessement skills; (b) confidence in performing these skills; and (c) confidence in recognizing abnormalities on health assessment. The reasons most often cited for infrequent skill use were "inappropriate to clinical setting" and "used only if problem suspected". The majority of participants agreed that the course met their needs. Implications for practice include administrative support for continuing education at other centres to enhance health assessment skills of ACNPs.